Crystallographic orientation-dependent deformation characteristics of additive manufactured interstitial-strengthened high entropy alloys. (1st January 2023) - Zhang, Wei; Shen, Jiajia; Oliveira, J.P.; Kooi, Bart J.; Pei, Yutao
Abstract: In this study, laser powder bed fusion (LPBF) was used for the fabrication of an interstitial-strengthened high entropy alloy (iHEA), Fe49.5 Mn30 Co10 Cr10 C0.5 (at.%). The as-fabricated iHEA possesses excellent strength-ductility synergy during tensile loading, with fracture strength reaching up to 1109 MPa at 37% engineering strain. Electron backscatter diffraction (EBSD) and high energy synchrotron X-ray diffraction were used to evaluate the microstructural characteristics of the material. In-situ EBSD analysis during uniaxial tensile testing was performed to unveil the deformation mechanisms. Moreover, crystallographic orientation-specific micropillar compression tests were conducted to determine how the grain deformation characteristics differ between orientations. Due to the activation of multiple slip systems and the homogeneous plastic flow, the [111] orientation demonstrated a higher yield strength and continuous work hardening rate. This research helps in clarifying grain orientation-specific contributions to the bulk mechanical response of additively manufactured HEA. Graphical abstract: Image, graphical abstract